FIXED COMBINATION OF THE CALCIUM CHANNEL BLOCKER LERCANIDIPINE AND ANGIOTENSIN CONVERTING ENZYME INHIBITOR ENALAPRIL: POSSIBILITY OF USAGE - O. D. Ostroumova (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2015)
Data on the updated approach to the choice of two-component antihypertensive combinations for different clinical situations are presented. Advantages and indications for combination of an angiotensin converting enzyme (ACE) inhibitor and dihydropyridine calcium antagonist are considered. Data on the efficacy and safety of the combination of calcium antagonist of the third generation, lercanidipine, and ACE inhibitor, enalapril, are presented.